An empirical examination of the influencers of premature decline of African clusters: Evidence from textile clusters in Ghana - Lydia Asare-Kyire; He Zheng; Ackah Owusu (South African Journal of Business Management, 2019)
Background: Comparatively, industry clusters in Africa have retrogressed over the years while their counterparts in Asia, Europe and America serve as engines for innovation and economic development. The textile industry cluster in most African economies has been threatened and is negatively affecting productivity, employment and revenue generation. Their survival, growth and sustainability are critical because of the sector's contribution to national developmentObjective: In this ariticle we investigate the role fators such as stakeholder relation among actors in the textile ecosystem, influence of supply chain networks, third-party pressures and technological changes affected the development of textile clusters in Ghana and how the country can rebuild the clusters.Method: Using partial least-square structural equation modelling techninque, we tested theoritical hypotheses using survey data from firms in the industrial enclave of Ghana.Result: The findings from the study acknowledges a sharp decline in the productivity and performance of firms in various industrial sectors especially the textile cluster. The influx of copycat products coupled with the firm's inability to adapt to changing production technology have been a key influencer in the deteriorating state of the textile industries. Again, gaps in stakeholder interactions and underutilised supply chain networks create bottlenecks that hinder the competitiveness and performance of these enterprises.Conclusion: On the contrary, findings from our study suggest external pressure from donors, multinationals and political influencers do not affect the performance and competitiveness of the textile sector as suggested by previous studies. Resuscitating the industry sector requires deliberate effort to improve coordination, information and technology sharing between key actors.
Keywords: 650